The Effect of Industrial Sector and Transportation Sector on CO2 Emissions In Indonesia - Izmi Dwi Maharani Poetri, Izmi Dwi Maharani Poetri (AFEBI Economic and Finance Review, 2021)
Environmental quality is an important aspect of life. This study aims to analyze the effect of industrial sector GDP and transportation sector GDP on environmental quality in terms of carbon dioxide emissions in Indonesia. This analysis uses multiple linear regression models with the Ordinary Least Square (OLS) method. The results of the analysis show that the GDP of the Industrial Sector has no significant effect on CO2 emissions, while Transportation GDP has a significant and positive effect on CO2 emissions, this is supported by the Environmental Kuznet Curve (EKC) theory. Keywords : carbondioxyde emission, GDP of industry sector, GDP of transportation sector